Solvent Optimization Studies for a New EURO-GANEX Process with 2, 2'-Oxybis(N, N-di-n-decylpropanamide) (mTDDGA) and Its Radiolysis Products. Issue 1 (2nd January 2023) - Verlinden, Bart; Wilden, Andreas; Van Hecke, Karen; J. M. Egberink, Richard; Huskens, Jurriaan; Verboom, Willem; Hupert, Michelle; Weßling, Patrik; Geist, Andreas; Panak, Petra J.; Hermans, Rainier; Verwerft, Marc; et al.
ABSTRACT: The diglycolamide 2, 2'-oxybis( N, N -di- n -decylpropanamide) (mTDDGA) is being studied as an extractant for actinides and lanthanides in the European Grouped Actinide Extraction (EURO-GANEX) process. The aim is the development of a more simplified process using a single extractant instead of a mixture of extractants used in the current EURO-GANEX process. This work presents solvent optimization studies of mTDDGA, with regards to the extraction characteristics of the different diastereomers of mTDGA and of mixed diastereomer solutions. Also radiolysis behavior has been studied by irradiation of solvent extraction systems in a gamma irradiation facility using 60 Co. The availability of irradiated organic solutions made it possible to gain valuable insights into the plutonium loading capacity after gamma-irradiation of the solvent up to 445 kGy and to quantify degradation compounds. Solvent extraction characteristic of the major degradation compounds themselves were determined. Like other methylated diglycolamides, we found a remarkable difference in extraction of up to two orders of magnitude between the two diastereomers. High plutonium loading (36 g L −1 ) is feasible using this single extractant, even after absorbing a dose of 445 kGy. This remarkable observation is possibly promoted by the presence of the main degradation compound which extracts plutonium verywell.